High-resolution SNP genotyping provides insight into the introduction and dissemination of Grapevine flavescence dorée phytoplasma in Switzerland - Cadena i Canals, Jasmine; Debonneville, Christophe; Dubuis, Nathalie; Kellenberger, Isabelle; Mandelli, Léa; Jeanrenaud, Michel; Viret, Olivier; Schumpp, Olivier (Frontiers in Plant Science, 2026)
Flavescence dorée is a quarantine grapevine disease transmitted by Scaphoideus titanus that was first detected north of the Swiss Alps in 2015 and has since progressively spread in western Switzerland, while its introduction routes and local dissemination dynamics remained poorly understood. To clarify these processes, we applied a molecular epidemiology approach combining MLST based on established markers (map, dnaK, vmpA, malG) with high-resolution SNP genotyping using newly developed loci to investigate FDp spatiotemporal dynamics and genetic diversity. Between 2015 and 2022, 4,212 symptomatic grapevines were sampled across Vaud, Valais, and Geneva, of which 26.3% tested positive for FDp. Established markers revealed highly homogeneous profiles, with all samples sharing the same genotypes (map M54, dnaK1, vmpA group II), supporting introduction through infected planting material. The malG locus alone distinguished only three profiles, but when combined with eight novel SNP markers, nine multilocus genotypes were identified, providing a finer resolution of FDp population structure. Our results provide the first genome-informed overview of FDp epidemiology in Swiss vineyards north of the Alps, highlighting the combined roles of planting material and local dissemination in shaping epidemic dynamics. The newly identified SNP markers enhance genotyping resolution and provide valuable tools for investigating phytoplasma spread and improving future surveillance strategies.